Experiences of Indonesian nurses in improving preterm oral feeding readiness in special care units: A qualitative descriptive study - Dyah Dwi Astuti; Rinawati Rohsiswatmo; Dessie Wanda; Diah Mulyawati Utari (Belitung Nursing Journal, 2023)
Background: Many preterm infants face feeding difficulties during the transition from enteral to oral feeding due to organ immaturity, resulting in aspiration, airway instability, and oral feeding intolerance. These challenges can increase morbidity and mortality among preterm infants. Nurses play a vital role in providing interventions to minimize negative impacts and enhance the safety of preterm oral feeding. Objective: This study aimed to explore the experiences of Indonesian nurses in improving preterm oral feeding readiness. Methods: A qualitative descriptive study was conducted involving ten nurses working in intensive care units as participants through purposive sampling. Data were collected through semi-structured, in-depth interviews conducted from January to March 2023. Thematic analysis was applied for data analysis. Results: Four key themes developed in this study: 1) comprehensive and holistic nursing assessment, 2) challenging and complex nursing issues, 3) the need for nutritional management skills, and 4) the necessity of collaborative support. Conclusion: Nurses play a pivotal role in enhancing oral feeding readiness among premature infants. Their responsibilities include assessing oral feeding readiness, addressing nursing challenges, and implementing multidisciplinary stimulation involving parents. This study provides a foundational framework for developing interventions to improve preterm oral feeding readiness.